Lower limb electromyographic characteristics and implications of taekwondo roundhouse kick “hit” and “miss” actions - Sun, Jianbo; Wang, Yifei; Dong, Delong (Frontiers in Bioengineering and Biotechnology, 2024)
To compare the muscular characteristics of "hit" and "miss" actions in roundhouse kicks among taekwondo athletes, and explore the similarities, differences, and implications for training, motion tests were conducted on ten taekwondo athletes using Noraxon32 and VICON. The results showed no significant differences (p > 0.05) in integrated electromyography (EMG) during the initiation and kicking phases between "miss" and "hit" actions. However, during the retraction phase, significant differences (p < 0.05) were observed in the left rectus femoris, left peroneus longus, right biceps femoris, right semitendinosus, and right tibialis anterior muscles. The tibialis anterior muscle of the swinging leg was activated first in the "hit" action, while the biceps femoris was activated first in the "miss" action.The supporting-side rectus femoris was activated first in the "hit" action, whereas it was the biceps femoris in the "miss" action. In both techniques, the gluteus maximus was the last muscle to be activated. The "miss" action had a longer cycle, and the duration of muscle work was longer than in the "hit" action. During the retraction phase of the front leg roundhouse kick, the muscles worked more than during the kicking phase, with the erector spinae and tibialis anterior being the core force-producing muscles in both techniques, characterized by high EMG values and long activation times. In the "miss" action, the thigh muscles drove the calf muscles, while the "hit" action exhibited the opposite pattern. "Hit" actions had a faster cycle compared to "miss," with greater force generation in "miss." The hip flexors and knee extensors of the kicking leg were the core force-producing muscles during the kicking process, determining the effectiveness and completion of the action.